Ultrasonographic Findings of Brain in Perinatal Asphyxiated Babies - Rahman, M Luthfor; Shah, Kabiruzzaman; Paul, Parimal K; Haq, Sanaul; Uddin, M Belal; Bari, Iqbal (TAJ: Journal of Teachers Association, 2018)
Perinatal asphyxia is a major cause of morbidity and mortality among the newborns in developing countries like Bangladesh. The CNS lesions following perinatal asphyxia can be detected by ultrasonography before closure of fontanels which is easier, cost-effective, and convenient than other methods like CT scan and MRI. This cross-sectional type of descriptive study was conducted on 99 perinatal asphyxiated babies in the Paediatric department of Rajshahi Medical College Hospital during the period of July 2008 to June 2010 to assess CNS lesions in different grades of HIE in term and preterm babies. A non-random purposive sampling method was adopted to select the sample unit. Ultrasonography of the brain of each patient was done at the Centre for Nuclear Medicine & Ultrasound, Rajshahi only once within first 28 days of life when the baby became clinically stable. Ultrasonographic findings showed that 13.1% term babies had abnormal findings of which cerebral edema occupied the major portions (54.54 %). About 20.0% preterm babies had abnormal ultrasonographic findings of which ventriculomegaly without IVH (66.6%).The study also showed that the prevalence of intracranial abnormality was higher (78.6%) among the perinatal asphyxiated babies with HIE stage-2 in comparison to that of the HIE stage-3 (14.3%) and HIE stage-1(7.1%).So, this study provided evidences in favour of role of ultrasonography of brain in the evaluation of perinatal asphyxiated babies and designing appropriate management. TAJ 2016; 29(2): 21-25